Adherence in the treatment of patients with extensively drug-resistant tuberculosis and HIV in South Africa: a prospective cohort study - OʼDonnell, Max R; Wolf, Allison; Werner, Lise; Horsburgh, C Robert; Padayatchi, Nesri (Journal of acquired immune deficiency syndromes (1999), 2014)
Extensively drug-resistant tuberculosis (XDR-TB)/HIV coinfection is difficult to treat with frequent adverse drug reactions and associated with high mortality. Adherence to antiretroviral therapy (ARV) and second-line TB medications may reduce mortality, prevent amplification of drug resistance, and improve outcomes. Prospective cohort study of XDR-TB patients on treatment in KwaZulu-Natal, South Africa. Adherence to ARV and TB medications was assessed separately at baseline and monthly. Knowledge, attitudes, and beliefs were assessed at baseline. Optimal adherence was defined as self-report of taking all pills in the previous 7 days; missing any pills was defined as suboptimal adherence. Primary outcome was optimal adherence 6 months after initiation of XDR-TB treatment to TB medications, ARV, and both ("dual adherence"). One hundred four XDR-TB patients (79.8% HIV coinfected, 84.3% on ARV at enrollment) were enrolled and followed monthly (median 8 visits; interquartile range: 4-12). Six-month optimal adherence was higher for ARV (88.2%) than TB medications (67.7%) (P < 0.001). Low educational attainment, male gender, and year of enrollment were independently associated with dual suboptimal adherence. At baseline, participants indicated that XDR-TB was curable (76.0%), HIV and TB were linked (81.7%), and ARV improves TB outcomes (72.1%). Baseline knowledge, attitudes, and beliefs did not predict subsequent adherence. Medication adherence was significantly higher for ARV than for TB medications in this cohort. Short-course treatment regimens for drug-resistant TB with lower pill burden may increase adherence and improve outcomes in XDR-TB/HIV. Programmatic support for dual adherence is critical in the treatment of drug-resistant TB and HIV.